Tremella fuciformis beverage improves glycated hemoglobin A1c and waist circumference in overweight/obese prediabetic subjects: a randomized controlled trial - Sawika Gitsomboon; Ganista Ratanapornsompong; Boonsong Ongphiphadhanakul; Supranee Thongpradit; Suwannee Chanprasertyothin; La-or Chailurtkit; Hataikarn Nimitphong (BMC Nutrition, 2024)
Abstract Background Prediabetes is increasing worldwide. Previous studies have demonstrated the potential of β-glucan derived from oat or barley to lower blood glucose, body weight, and plasma lipid levels. These findings offer a potentially attractive strategy for reducing the risk of diabetes in prediabetic individuals. However, the effects of β-glucan from Tremella fuciformis on glucose metabolism and anthropometric measurements in humans have yet to be studied. We hypothesized that β-glucan from Tremella fuciformis may improve metabolic parameters in subjects with prediabetes. This study aimed to investigate the effects of a once-daily beverage containing Tremella fuciformis (snow mushroom) on anthropometric measurements, metabolic biomarkers, and insulin sensitivity in overweight/obese subjects with prediabetes. Methods In this double-blind RCT, 56 participants were randomly assigned to receive either a Tremella fuciformis beverage or placebo daily for 12 weeks. All parameters were assessed at baseline and after the intervention. Results After 12 weeks, participants in the intervention group exhibited significant improvements in glycated hemoglobin A1c (HbA1C; 6.03 ± 0.26% at baseline vs. 5.96 ± 0.25% at 12 weeks, p = 0.047, Cohen’s d = 0.39) and waist circumference (95.2 ± 12.51 cm at baseline vs. 93.46 ± 11.48 cm at 12 weeks, p = 0.022, Cohen’s d = 0.45). There were no adverse events reported. Conclusion This exploratory study demonstrated that Tremella fuciformis beverage consumption may improve HbA1C and waist circumference in overweight/obese prediabetic individuals. Further research, including larger-scale RCTs and mechanistic studies, is needed to confirm these findings and optimize the therapeutic potential of Tremella fuciformis derivatives in managing prediabetes and preventing type 2 diabetes. Trial registration Registered in Thai Clinical Trials Registry (14/07/2021, TCTR20210714004).